The Fallacies of Lord Keynes' General Theory: Reply - Rueff, Jacques (Quarterly Journal of Economics, 1948)
Journal Article The Fallacies of Lord Keynes' General Theory: Reply Get access Jacques Rueff Jacques Rueff Institut d'Études Politiques, Paris Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 62, Issue 5, November 1948, Pages 771–782, https://doi.org/10.2307/1883471 Published: 01 November 1948